Solution structures of polcalcin Phl p 7 in three ligation states: Apo‐, hemi‐Mg2+‐bound, and fully Ca2+‐bound. Issue 2 (12th November 2012) - Henzl, Michael T.; Sirianni, Arthur G.; Wycoff, Wei G.; Tan, Anmin; Tanner, John J.
Abstract Polcalcins are small EF‐hand proteins believed to assist in regulating pollen‐tube growth. Phl p 7, from timothy grass (Phleum pratense), crystallizes as a domain‐swapped dimer at low pH. This study describes the solution structures of the recombinant protein in buffered saline at pH 6.0, containing either 5.0 mM EDTA, 5.0 mM Mg2+, or 100 μM Ca2+. Phl p 7 is monomeric in all three ligation states. In the apo‐form, both EF‐hand motifs reside in the closed conformation, with roughly antiparallel N‐ and C‐terminal helical segments. In 5.0 mM Mg2+, the divalent ion is bound by EF‐hand 2, perturbing interhelical angles and imposing more regular helical structure. The structure of Ca2+‐bound Phl p 7 resembles that previously reported for Bet v 4—likewise exposing apolar surface to the solvent. Occluded in the apo‐ and Mg2+‐bound forms, this surface presumably provides the docking site for Phl p 7 targets. Unlike Bet v 4, EF‐hand 2 in Phl p 7 includes five potential anionic ligands, due to replacement of the consensus serine residue at –x (residue 55 in Phl p 7) with aspartate. In the Phl p 7 crystal structure, D55 functions as a helix cap for helix D. In solution, however, D55 apparently serves as a ligand to the bound Ca2+. When Mg2+ resides in site 2, the D55 carboxylate withdraws to a distance consistent with a role as an outer‐sphere ligand. 15N relaxation data, collected at 600 MHz, indicate that backbone mobility is limited in all three ligation states. Proteins 2013. © 2012 Wiley Periodicals, Inc.